PENGARUH UTANG TERHADAP LABA BERSIH PT INDOCEMENT TUNGGAL PRAKASA TBK TAHUN 2021 - Nurdin Zaelani Apdau; Riko Sutriyadi; Nasril Nasril (JURNAL LENTERA AKUNTANSI, 2021)
With the rapid growth of the present day, every company is required to be able to compete with other companies in establishing the development and the existing rates. The company's growth and progress are determined in how it achieves its ultimate goal of achieving its established profit. In this case debt isa source of funds to continue production and achieve the company's goals. The thesis marked "the effects of debt on net profit PT Indocement Tunggal Prakasa Tbk. And the study commissioned to know how debt affects a partial and large net profit PT Indocement Tunggal Prakasa Tbk registered to the Indonesia Stock Exchange. The method used in this study is with a quantitative approach with secondary data as a source of data obtained from the official site of the Indonesian exchange. The technique used was a classic analysis of assumptions, a simple hypothetical and regression analysis with the help of SPSS software. Based on a study conducted by t or partial by the SPSS it is concluded that debt has a negative effect on net profit.Keywords: net profit, debt, Indocement Tunggal Prakasa